2021
DOI: 10.1016/j.brs.2021.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Multi-electrode stimulation evokes consistent spatial patterns of phosphenes and improves phosphene mapping in blind subjects

Abstract: Background: Visual cortical prostheses (VCPs) have the potential to restore visual function to patients with acquired blindness. Successful implementation of VCPs requires the ability to reliably map the location of the phosphene produced by stimulation of each implanted electrode. Objective: To evaluate the efficacy of different approaches to phosphene mapping and propose simple improvements to mapping strategy. Methods: We stimulated electrodes implanted in the visual cortex of five blind and fifteen sighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…To improve the clarity of images produced by stimulating through multiple electrodes, recent studies tested a stimulation paradigm that sequentially and rapidly stimulated individual electrodes placed on human visual cortex (Beauchamp et al 2020; Oswalt et al 2021). They found that sequential stimulation produced shapes that were recognized more quickly and accurately than traditional simultaneous stimulation of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the clarity of images produced by stimulating through multiple electrodes, recent studies tested a stimulation paradigm that sequentially and rapidly stimulated individual electrodes placed on human visual cortex (Beauchamp et al 2020; Oswalt et al 2021). They found that sequential stimulation produced shapes that were recognized more quickly and accurately than traditional simultaneous stimulation of electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the following 2 fixation methods were employed: (I) unimanual fixation, in which a single index finger was placed on a tactile fixation point; (II) bimanual fixation, in which the right index finger on left was overlaid on the tactile point. Additionally, by comparing absolute mapping (the stimulation of a single electrode) and relative mapping (the stimulation of 3 to 5 phosphenes), researchers found that bimanual fixation related relative mapping strategies resulted in the most precise estimates of phosphene organization (76). In conclusion, the above-mentioned techniques, together with a standard logarithmic model of visual cortex, may provide a practical way to improve the implementation of a CVP.…”
Section: Orionmentioning
confidence: 98%
“…This means that some non-linear dynamics might be missed. Also, several studies reported that higher stimulation amplitudes may give rise to double phosphenes (18,19,23,77), or a reduction of phosphene brightness (23). Furthermore, interactions between simultaneous stimulation of multiple electrodes can have an effect on the phosphene size and sometimes lead to unexpected percepts (6).…”
Section: M2 Complexity and Realism Of The Simulationmentioning
confidence: 99%